Social Cohesion and the Public Ministry in Latin America - Pásara, Luis (2009)
This paper is about the Public Ministry and the social cohesion in the way that the work of this entity contributes to the strengthening of the democracy. The author proposes the abstraction of the differences that this entity could have in each country and to establish common areas of elaboration. Furthermore, he points that the Public Ministry behavior or its institutional development do not be framed into its legal base of action, even when could have a correlation. The author emphasizes that its behavior must not see as an exercise of power, however as a service to achieve the social cohesion. He mentions that the current performance is far away to achieve the social cohesion, it be said that there is a selective treatment of cases that do not help to promote the citizen confidence. In this way, the deficient fight against the impunity along with the abuse of power undermine the democracy and the strengthening of the social cohesion. For it, he suggest lines of action, by which the Public Ministry could contributes to the social cohesion.  The first, the access to the justice. The accident geography of each country and the discrimination had to been consider as main factors that denied the access to the justice. Likewise, it must do an efficient use of the resources that each entity had. The second, to fight against the impunity. The impunity promotes crime and origins that alternative ways are planted, legal or illegal, as a way to reach the compliance of the rules. The third, transparency of the discretion. The decisions of the authorities must be motivated due to the citizen could know the reasons of each one. This is a way to legitimate the authority performance. The last one, to fight the abuse of power. The equal treatment to the people is a fundamental right violated when there are preferences in the treatment. This situation encourages the corruptions and breach the democratic system we live in. Finally, the author mentions that we have ask ourselves how the work of the Public Ministry was to focus its development on the proposed lines of action. The behavior adopted should had to been exercised with independence, as an entity’s policies of action and in coordination inside the judicial system.